O Brasil diz sim às armas de fogo: uma análise sobre o referendo do desarmamento - Esteves, Eulícia (2007)
This work a nalyses the electoral process of the referendum on the prohibition of the commercialization of firearms and ammunition in Brazil through the perceptions and motivations of the voters. Using as its source of data the letters of readers of three major newspapers in Brazil, it is intended to identify the main values, feelings and arguments put forward to justify voting. It thus presents several considerations on political culture, the culture of fear, and perceptions of insecurity and citizenship in Brazil.